(untitled) (Al-Qamar, 2021)
Covid-19 significantly reflected an impact on social, cognitive and psychological realities of youth during the complete lock down phase around the globe. The new normal brought many cultural and social barriers that influenced basic believes of health, media, religion, romantic, social and academic life of university students. This study explores the level of gratification among youth through the sources of satisfaction through quantitative research using random sampling technique. A survey is conducted from the 598 University students with the scale of (SWLS). The findings of the study reveals that there is significant association between life satisfaction and romantic relationship, health, academic performance, media and achievement while there is no relationship between life satisfaction, social contact and religion. The researcher has used Uses and Gratification Theory as a framework for the analysis of the current relevance life satisfaction. The findings also conclude that there is difference in gender and life satisfaction whereas no difference has been found between living arrangement and life satisfaction. Moreover, the results also revealed that there is association between family income and life satisfaction. This study highlights the importance of health, romantic relationship, media, religion, social contact, academic performance and achievement in our lives.